Effectiveness of the Family Hope Program in Cikijing District, Majalengka Regency: Case Study in Bagjasari Village - Restita, Dede; Permana, Ipik; Hidayat, M. Taufik (ann4publisher@gmail.com, 2023)
Poverty is a multidimensional problem commonly occurring in various parts of the world, including Indonesia. The government must immediately carry out poverty alleviation and immediately break the chain of causes. One of the steps taken by the government to overcome poverty is the Family Hope Program (PKH). Welfare is the ultimate goal of the Family Hope Program, which is to improve the quality of life for Very Poor Families (KSM). With the implementation of PKH, it is hoped that it can improve people's living standards in the socio-economic, health, and public education fields, especially for people experiencing poverty. The purpose of this study was to determine the effectiveness of the Family Hope Program, the obstacles faced, and the efforts to overcome them in Bagjasari Village, Cikijing District, Majalengka Regency. The theoretical approach used is the Saxena effectiveness theory approach. The research method used is a descriptive research method with a qualitative approach. Data was collected by observation and in-depth interviews. The results showed that the effectiveness of the Family Hope Program in Bagjasari Village, Cikijing District, Majalengka Regency, still needed to be more optimal, as seen from the uneven target of the recipients of the Family Hope Program (PKH). Also, the distribution time and the Family Hope Program (PKH) were often hampered.